Relationship between the level of physical activity and its reflections on the mental health and quality of life of the population during the COVID-19 pandemic (Research, Society and Development, 2022)
The decrease in physical activity levels, the increase in stress and the drop in social life are directly related to the reduction of quality of life. The aim of the present study was to verify whether the level of physical activity affects the quality of life of adults during the COVID-19 pandemic. A descriptive study was carried out with individuals of both genders, with three questionnaires being applied, one that assesses the level of physical activity (IPAQ), the other that analyzes the subjective perception of quality of life (WHOQOL) and a third that assesses the perception of the effect of the pandemic on quality of life. It was seen that 46.16% of the participants were not very active; approximately 65% reported worsening in mental health and quality of life, with changes in the physical, environmental and social domains being observed. It was not possible to relate the practice of physical activity and good quality of life indices, but it is observed that the pandemic negatively influenced the mental health and quality of life of the population. New studies and new analyzes are needed to better understand this relationship between quality of life and physical activity in a pandemic scenario.